Domestic violence: a hidden barrier to contraceptive use among women in Nigeria - Bishwajit G; Yaya S (Dove Medical Press, 2018)
Ghose Bishwajit, Sanni Yaya Faculty of Social Sciences, School of International Development and Global Studies, University of Ottawa, Ottawa, ON, Canada Background: The nonuse of family planning methods remains a major public health concern in the low-and-middle-income countries, especially due to its impact on unwanted pregnancy, high rate of abortion, and transmission of sexually transmitted diseases. Various demographic and socioeconomic factors have been reported to be associated with the nonuse of family planning methods. In the present study, we aimed at assessing the influence of domestic violence (DV) on contraceptive use among ever married women in Nigeria. Methods: Data on 22,275 women aged between 15 and 49 years were collected from the most recent Nigeria Demographic and Health Survey conducted in 2013. The outcome variable was contraceptive utilization status, and the main exposure variable was DV, which was assessed by the self-reported experience of physical and psychological abuse. Complex survey method was employed to account for the multistage design of the survey. Data analyses were performed by using bivariate and multivariable techniques. Results: The mean age of the participants was 31.33±8.26. More than four fifths (84%) of the participants reported that they were not using any contraceptive methods at all. Lifetime prevalence of psychological and physical abuse was, respectively, 19.0% (95% CI =18.0–20.1) and 14.1% (95% CI =13.3–14.9). Women who reported physical abuse were 28% (adjusted odds ratio [AOR] =1.275; 95% CI =1.030–1.578), and those reported both physical and psychological abuse had 52% (AOR =1.520; 95% CI =1.132–2.042) higher odds of not using any contraception. Conclusion: The rate of contraception nonuse was considerably high and was found to be significantly associated with DV. Thus, the high prevalence of DV may compromise the effectiveness of the family planning programs in the long run. Evidence-based intervention strategies should be developed to protect the health and reproductive rights of the vulnerable women and to reduce DV by giving the issue a wider recognition in public policy making. Keywords: contraceptive non-use, demographic and health survey, spousal violence, physical abuse, psychological abuse